2019
DOI: 10.15446/agron.colomb.v37n2.72765
|View full text |Cite
|
Sign up to set email alerts
|

Different soaking times and niacin concentrations affect yield of upland rice under water deficit conditions

Abstract: Rice is an important source of energy for a large part of the world’s population. The development and application of technologies that contribute to the improvement of production forthis grain have great importance. The objective of this study was to evaluate the influence of rice seed immersion in a niacin solution on plant development, physiology and production. Thetreatments were defined by a combination of two immersion times for the seeds (12 h and 24 h) in four niacin concentrations (0.00, 100, 200 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The application of nicotinamide increases the leaf area of vegetables, as observed for the corn crop (Colla et al, 2021). This increase is related to the activity of the photosynthetic system (Vendruscolo et al, 2019), which increases energy reserves (Abdelhamid et al, 2013). These reserves can be used during periods when the plant undergoes stress, but it is also essential for the development of new organs, such as leaves, stems, and roots, in addition to the expansion of the cells that make up these structures (Berglund et al, 2017;Dawood et al, 2019;El-Lethy et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The application of nicotinamide increases the leaf area of vegetables, as observed for the corn crop (Colla et al, 2021). This increase is related to the activity of the photosynthetic system (Vendruscolo et al, 2019), which increases energy reserves (Abdelhamid et al, 2013). These reserves can be used during periods when the plant undergoes stress, but it is also essential for the development of new organs, such as leaves, stems, and roots, in addition to the expansion of the cells that make up these structures (Berglund et al, 2017;Dawood et al, 2019;El-Lethy et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Other authors observed that the application of thiamine at different concentrations effectively affects and favors the development of rice plants (Vendruscolo et al, 2019) and sweet corn (Vendruscolo et al, 2018), especially when the plants are subjected to abiotic stresses or field production conditions, where environmental factors act on the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of excessive use of soil and water resources can be reduced by applying alternative solutions that allow maintaining development without further damage to natural resources. The exogenous application of vitamins in plants can lead to increase in vigor, higher reproductive rates, and resistance to edaphoclimatic conditions (Contieri et al, 2018;Vendruscolo et al, 2019), among other physiological increments that allow cultivation under conditions of increased stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vitamin is present in the constitution will of coenzymes NADH and NADPH, which are associated with the reduction of enzymatic oxidation reactions in living cells. So naturally, nicotinamide concentration can increase in plants after situations that cause oxidative stress and induction of defensive metabolism (BERGLUND & OHLSSON 1995, VENDRUSCOLO et al 2019a.…”
mentioning
confidence: 99%